Völkisches Denken 1848 bis 1948 Von der Paulskirche über Weimar zum Petersberg - Reitzenstein, Julien; Rusinek, Bernd-A; Rupnow, Dirk (Politik - Ideologie - Wissenschaft, 2023)
The emergence of parliamentary democracy and the political public sphere in Germany in the nineteenth century created the conditions for the development of collective ideological vocabulary. From the Frankfurt Parliament to the interwar period, this volume shines light on "völkisch" thinking in the semantic battle for concepts such as "Volk" and "nation," as well as practices of inclusion and exclusion like "Germanophilia" and anti-Semitism.